Hotspots evolution and frontiers of immunotherapy for the treatment of acute myeloid leukemia: A bibliometric analysis - Nana Zhe; Qiang Li; Nanqu Huang; Hang Li; Hongyun Chen; Pinwei Zhu (Human Vaccines & Immunotherapeutics)
Given the growing significance of immunotherapy in addressing the limitations of conventional acute myeloid leukemia (AML) treatments, this study aimed to elucidate the hotspot evolution and frontiers of immunotherapy in AML using bibliometric analysis. With a strict retrieval strategy applied in the Web of Science Core Collection, 2411 publications were obtained and exported. The temporal and geographical distributions of these publications and the countries, institutions, journals, and authors who contributed to the field were investigated. An in-depth content analysis was performed. The United States had various research institutions dedicated to AML immunotherapy. Frontiers in Immunology had the highest number of publications, but Blood had the highest H-index. Marion Subklewe was the most productive author. The current research hotspots of AML immunotherapy included chimeric antigen receptor-T-cell therapy, antibody-based immunotherapies, immune checkpoint blockade, and combination therapy, highlighting the key aspects of immunotherapy for AML treatment and providing comprehensive insights into the research status and advances in this field. Novel immunotherapies combined with chemotherapy may become the primary focus of AML treatment.